Inhibition of debrisoquine hydroxylation with quinidine in subjects with three or more functional CYP2D6 genes - Dalén, P (Blackwell Science Inc, 2000)
AIMS: To study whether the CYP2D6 capacity in ultrarapid metabolizers of debrisoquine due to duplication/multiduplication of a functional CYP2D6 gene, can be ‘normalised’ by low doses of the CYP2D6 inhibitor quinidine and whether this is dose-dependent. METHODS: Five ultrarapid metabolizers of debrisoquine with 3, 4 or 13 functional CYP2D6 genes were given single oral doses of 5, 10, 20, 40, 80 and 160 mg quinidine. Four hours after quinidine intake, 10 mg debrisoquine was given. Urine was collected for 6 h after debrisoquine administration. Debrisoquine and its 4-hydroxymetabolite were analysed by h.p.l.c. and the debrisoquine metabolic ratio (MR) was calculated. RESULTS: Without quinidine the MR in the ultrarapid metabolizers ranged between 0.01 and 0.07. A dose-effect relationship could be established for quinidine with regard to the inhibitory effect on CYP2D6 activity. To reach an MR of 1–2, subjects with 3 or 4 functional genes required a quinidine dose of about 40 mg, while the sister and brother with 13 functional genes required about 80 mg quinidine. After 160 mg quinidine, the MRs, in the subjects with 3, 3, 4, 13 and 13 functional genes, were 12.6, 10.1, 9.2, 2.4 and 2.2, respectively. CONCLUSIONS: A dose-effect relationship could be established for quinidine inhibition of CYP2D6 in ultrarapid metabolizers. The clinical use of low doses of quinidine as an inhibitor of CYP2D6 might be considered in ultrarapid metabolizers taking CYP2D6 metabolized drugs rather than giving increased doses of the drug. Normalizing the metabolic capacity of CYP2D6, by giving a low dose of quinidine, may solve the problem of ‘treatment resistance’ caused by ultrarapid metabolism.